Program Merdeka Belajar - Suprihadi Suprihadi (Syntax Idea)
Education in Indonesia continues to experience changes along with technological developments. The development of theory and the responsibility of stakeholders so that the education system continues to be developed for future generations who are responsive to all the challenges of current formation technology. Therefore, the community, in this case the younger generation, must have creativity and be able to respond to developments in information technology so that the community, through the younger generation, remains the main actor in carrying out a sustainable life as information technology develops throughout the world. The Ministry of Education and Culture has established an independent campus to study for developing a learning concept for educators to develop a student-centered learning system through the concept of independent learning on the independent campus. The results of this study explain the concept of independent learning for students of STIE SBI Yogyakarta in understanding the eight concepts of independent learning through the proposed hypothesis. The results of the hypothesis prove that the Free Learning Concept has a significant positive effect on learning the Free Learning Apprentice Concept, Entrepreneurship and Research and has a significant positive effect on students at the Independent Learning campus.